Carbon Stock and Change Rate under Different Grazing Management Practices in Semiarid Pastoral Ecosystem of Eastern Ethiopia - Gebremedhn, Haftay Hailu; Zewdu Kelkay, Tessema; Tesfay, Yayanshet; Tuffa, Samuel; Workeneh Dejene, Sintayehu; Mensah, Sylvanus; Mears Devenish, Adam John; Egeru, Anthony (Land, 2022)
Grazing management strategies tend to have different effects on rangeland plant production. Changes in grazing management can, therefore, affect the carbon stock potential of rangelands. Despite rangeland ecosystems being important global sinks for carbon, we know relatively little about the effect of traditional grazing management practices on their potential to store carbon. In this study, we evaluated the carbon stock and change rate of rangelands using three traditional grazing management practices in the semiarid pastoral ecosystem of eastern Ethiopia. By comparing data on vegetation and soil carbon stocks, we found that there was a strong significant difference (p < 0.001) between these different management practices. In particular, the establishment of enclosures was associated with an annual increase in carbon stocks of soil (3%) and woody (11.9%) and herbaceous (57.6%) biomass, when compared to communal open lands. Both enclosure and browsing management practices were found to have the highest levels of soil organic carbon stocks, differing only in terms of the amount of woody and herbaceous biomass. Thus, modest changes in traditional grazing management practices can play an important role in carbon storage and sequestration. Further research is required on a wider range of traditional pastoral management practices across space and time, as understanding these processes is key to combating global climate change.
Keywords: Open grazing; Enclosure; Browsing area; Climate change mitigation; Rangeland ecosystem services; Carbon stock